Shear Bond Strength of Saliva Contaminated and Re-etched All-in-One Adhesive to Enamel - M. Khoroushi; F. Mostajeran; Sh. Shayegh (Tehran University of Medical Sciences, 2008)
Objective: The aim of this study was to investigate the effect of phosphoric acid re-etching of an enamel surface treated via a one-bottle adhesive system on shear bond strength between resin composite and the enamelsurface in different stages of adhesive application. Materials and Methods: Extracted intact premolars (n=84) were divided into sevengroups (n=12). In the control group 1, the adhesive i-Bond was used according to the manufacturer's instructions, with nocontamination. In groups 2 to 4, the conditioned and saliva, contaminated enamel was blot dried only, rinsed,and blot dried, rinsed blot dried and re-etched, respectively. In groups 5, 6and 7 cured adhesive was contaminated with saliva and then rinsed and blot-dried, blot dried only and rinsed, blot-dried and re-etched respectively. In groups 3, 4, 6 and 7 the adhesive was reapplied. Afterward, Z100 compos-ite cylinders were bonded to the enamel surfaces. The samples were thermocycled (5°C and 55°C, 30 s, dwelling time: 10 s, 500 cycles). Finally, the samples were sheared using Dartec testing machine and shear bond strength data were subjected to one-way ANOVA analysis and Tukey's HSD test. Results: There were statistically significant differences among groups 1 and 5-7. The samples in groups 1 and 4 demonstrated higher bond strengths than those in the other groups. Conclusion: Using phosphoric acid etching may be effective, only where contamination occurs prior to curing of the adhesive. After curing of the adhesive, none of the methods in this study would be preferred.